Natural history of the common iliac artery in the presence of an abdominal aortic aneurysm. - Richards, T; Dharmadasa, A; Davies, R; Murphy, M; Perera, R; Walton, J (2009)
OBJECTIVE: Patients with an abdominal aortic aneurysm (AAA) often develop common iliac artery (CIA) aneurysms. We wished to assess the natural history of the CIA in the presence of an AAA and develop a model to predict CIA growth. METHODS: Data were gathered at a single center from 1996 to 2006 in patients undergoing AAA surveillance. Maximum size of AAA and both CIAs at yearly intervals were collected. CIA > 16 mm was defined as being an aneurysm. A mixed effects regression model was generated to predict CIA growth rates. RESULTS: One hundred ninety-one patients with AAA underwent duplex ultrasound on at least two occasions (median, 4; range, 2-11). Average baseline CIA was 12 mm (standard deviation, 5.0); 41% of patients had one CIA over 16 mm. A CIA > 16 mm was more likely to expand (81% vs 53%, P = .0001) particularly in patients with an AAA that expanded (73% vs 43%, P = .0005). A larger AAA was associated with a larger CIA (P = .0341). CIA growth rate was proportional to baseline size. A CIA of 16 mm was predicted to take 10 years to reach 25 mm (156% or 5.6% per annum) or if 23 mm at baseline 10 years to reach 35 mm (152% or 5.2% per annum). Overall, a CIA was predicted to increase in diameter by 5.7% (+/- 0.5%) per annum. CONCLUSION: The CIA in the presence of an AAA expands over time. CIA > 16 mm are more likely to increase. Routine duplex examination of a CIA less than 16 mm may not be necessary when following up AAA. These data may be used to aid planning and intervention during AAA repair.